Sensitivity and response times of doped tin oxide integrated gas sensors - Nayak M.S.; Dwivedi R.; Srivastava S.K. (My University, 2025)
This paper deals with the sensitivity and responses of fabricated integral gas sensors using thick film technology. Four different sensors were fabricated on a single substrate using tin oxide as the parent material, and dopings were done using ZnO, MoO and CdS. It was observed that N2 ambient is suitable as the background ambient for evaluation of characteristics of sensors. The fabricated sensors have shown varying sensitivity to hydrocarbons such as acetone, carbon tetrachloride, ethyl methyl ketone and xylene. © 1994.